Negative impact of disuse and unloading on tendon enthesis structure and function. (May 2021) - Roffino, S.; Camy, C.; Foucault-Bertaud, A.; Lamy, E.; Pithioux, M.; Chopard, A.
Abstract: Exposure to chronic skeletal muscle disuse and unloading that astronauts experience results in muscle deconditioning and bone remodeling. Tendons involved in the transmission of force from muscles to skeleton are also affected. Understanding the changes that occur in muscle, tendon, and bone is an essential step toward limiting or preventing the deleterious effects of chronic reduction in mechanical load. Numerous reviews have reported the effects of this reduction on both muscle and bone, and to a lesser extent on the tendon. However, none focused on the tendon enthesis, the tendon-to-bone attachment site. While the enthesis structure appears to be determined by mechanical stress, little is known about enthesis plasticity. Our review first looks at the relationship between entheses and mechanical stress, exploring how tensile and compressive loads determine and influence enthesis structure and composition. The second part of this review addresses the deleterious effects of skeletal muscle disuse and unloading on enthesis structure, composition, and function. We discuss the possibility that spaceflight-induced enthesis remodeling could impact both the capacity of the enthesis to withstand compressive stress and its potential weakness. Finally, we point out how altered compressive strength at entheses could expose astronauts to the risk of developing enthesopathies.